KUALITAS PELAYANAN PUBLIK (STUDI TERHADAP PELAYANAN KESEHATAN DI POLIKLINIK JIWA RUMAH SAKIT ERNALDI BAHAR PROVINSI SUMATERA SELATAN) - Yenny Ratnawaty; Andy Alfatih; Andries Lionardo (IKesT Muhammadiyah Palembang, 2024)
In recent years, attention to mental health has increased globally, with greater recognition of the importance of providing high-quality mental services. Ernaldi Bahar Hospital of South Sumatra Province is the only mental hospital in South Sumatra Province so that the services provided must be of high quality. Ernaldi Bahar Hospital psychiatric polyclinic is a polyclinic that provides health services for outpatients specialising in mental illness and psychiatry. In measuring the quality of health services provided, namely using the theory of Parasuraman et al (1990) with the dimensions of tangible, reliability, responsiveness, assurance and empathy. Method: This research was analysed using descriptive statistical methods using the gap analysis-IPA (Importance Performance Analysis) method which is described in a Cartesian diagram. This research is descriptive with a quantitative approach, data collection techniques using questionnaires distributed to 100 patient companion respondents selected using accidental sampling techniques. Results: From the analysis of the respondents' assessment of the quality of health services, a percentage value of 83.62% was obtained in the good category, but there was still a gap between the perceptions and expectations of respondents regarding the quality of health services where the results showed that health services at the Ernaldi Bahar Hospital Mental Polyclinic had not been able to meet the expectations of service users because it had a negative gap value in all indicators. From the results of the quadrant I Cartesian diagram, it shows that several service indicators must be improved with a high priority and in quadrant III, although the priority is low, it still needs to be improved so that the quality of service can be better.